Review of the Evidence on Short-Term Education and Skills Training Programs for Out-of-School Youth with a Focus on the Use of Incentives - Clarke, Marguerite; Sharma, Meghna; Bhattacharjee, Pradyumna (World Bank, Washington, DC, 2021)
Short-term education and skills training programs are a popular way to meet the needs of unemployed, out-of-school youth by providing them with an opportunity to quickly acquire qualifications and skills that can lead to productive employment. This paper reviews the global evidence to identify which programs are most effective at delivering results. How incentives for stakeholders are incorporated into the program design is given particular attention. Based on the findings, recommendations are offered for the future design of these training programs.